PENGARUH KECERDASAN EMOSIONAL, KEMAMPUAN SDM DAN EFEKTIVITAS PELAYANAN TERHADAP KINERJA ORGANISASI - Rini Kustiah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
This study design using quantitative and qualitative methods. Data were collected through questionnaires to 50 respondents officers in the Department of Population and Civil Registration North Barito regency. Program data analysis using SPSS version 16.0. Then analysis of the data obtained in the form of quantitative analysis Quantitative Analysis of covering validity and reliability, hypothesis testing through F test and t test and analysis test, the coefficient of determination (R2). The data analysis technique used is the analysis of multiple linear regersi which serves to prove the hypothesis of the study.Results of the analysis found that variables Emotional Intelligence (X1) of 56.2%, HR Capability (X2) of 69.8%, and Service Effectiveness (X3) amounted to 86.3% singly or together have a positive and significant impact on the Public Organization performance (Y). Figures adjusted R-square of 0.879 indicates that 87.9% of Public Organization Performance variables influenced by three independent variables used in the regression equation. While the remaining 12.1% is explained by other variables outside the three variables used in this study. And it is known that the dominant variable affecting the Public Organization Performance is variable effectiveness in addition to the variables Emotional Intelligence Service and the ability of human resources.